Hospital-acquired Skin and Skin-structure Infection in COVID-19 Infected Patient with Prolonged Hospitalization - Erni Juwita Nelwan; Rahajeng N Tunjungputri; Narottama Tunjung; Djoko Widodo (Interna Publishing, 2021)
Acute bacterial skin and skin-structure infections (ABSSSI) is defined in 2013 by the US Food and Drug Administration as a bacterial cellulitis/erysipelas, major skin abscesses, and wound infections. The Infectious Diseases Society of America (IDSA) in 2014 classifies skin and soft-tissue infection (SSTI) as either non-purulent (which includes cellulitis, erysipelas, and necrotizing infection) or purulent (including furuncle, carbuncle, and abscess). Among hospitalized patients with SSTI, healthcare-associated infections account for 73.5% of all cases. Notably, skin and skin-structure infections caused by Pseudomonas aeruginosa, a common hospital pathogen, was reported to cause higher total cost and longer hospital length of stay compared to non-P. aeruginosa cases, despite causing only approximately 5.7% of all healthcare-associated SSTIs. Infection with P. aeruginosa should always be considered in non-healing skin infections in patients with prolonged hospitalization and antibiotic exposure. Tissue culture, preferably taken by surgical debridement, should be promptly performed; and when hospital-infection is suspected, appropriate antibiotics should be started along with removal of all devitalized tissue and to promote skin and soft tissue healing. Expedited discharge should be considered when possible, with adequate antibiotic treatment and follow up for definitive wound treatment.